THE ANTI-SENSATIONAL PHENOMENON IN AFRICAN MASS MEDIA POLICIES - Ebokem-Fomenky (Fréquence Sud, 2021)
The increasing interest in the problems of the mass media in frica has, since independence, been parallelel by a gradual but constant refocusing of attention on barriers to their development. This is especially so when they tend to develop in directions others than desiredby each government concerned. In the last two decades or so, we have seen this interest in the mass media expand through the declared desire of African information ministers, journalists and policians to give policy priority position on the agenda of several international conferences (2). To the extent that most of the conferences were largely a reflection at the general revolutionary trend of thought (3) andthe level of social change in the Third World, the recent floodtide of interest in the development of the African mass media may not be exceptional. What is trange is the fact in most countries where the energizing influences of mass media development are being given primary attention, the libertarian motive in its traditional snse has World Information Order, a new information philosophy whose central theme has been summerized by a call for more accent to be placed on developmental newsreporting in the Third World.